1992
DOI: 10.1080/10168739200000023
|View full text |Cite
|
Sign up to set email alerts
|

The Role of International Trade in the Convergence of Per Capita GDP in the OECD: 1950–1985

Abstract: The convergence of per capita GDP is usually attributed to the flow of technology from the high per capita income to the low per capita income countries. This paper examines the role of international trade in the convergence process for 19 OECD countries during the period 1950-1985. The paper finds that: a) those countries starting with lower income increased their trade openness faster than the high income economies; and b) the countries that expanded trade faster grew more rapidly. These findings and the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Empirical studies have found that international trade has contributed to macro convergence among developed countries in the postwar era. Ben-David (1993) studies the contribution of trade to macro convergence in the European Union, and Rassekh (1992) in the OECD countries. Dollar and Wolff (1993) document the convergence of aggregate capital -labor ratios among advanced countries, suggesting a waning role of differences in their capital and labor endowments in international trade.…”
Section: Micro Convergence and Macro Convergence: Factor Price Equalimentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical studies have found that international trade has contributed to macro convergence among developed countries in the postwar era. Ben-David (1993) studies the contribution of trade to macro convergence in the European Union, and Rassekh (1992) in the OECD countries. Dollar and Wolff (1993) document the convergence of aggregate capital -labor ratios among advanced countries, suggesting a waning role of differences in their capital and labor endowments in international trade.…”
Section: Micro Convergence and Macro Convergence: Factor Price Equalimentioning
confidence: 99%
“…Dollar and Wolff (1993) present a thorough empirical analysis of micro convergence. For a survey of the theoretical and empirical works on factor price equalization and convergence, see Rassekh and Thompson (1993).…”
Section: Micro Convergencementioning
confidence: 99%
“…The empirical literature generally examines indirect evidence including trade volumes, trade openness, input ratios, relative production wages and per capita incomes as summarized by Deardorff (), Leamer () and Baldwin (). There is evidence of the predicted wage convergence across trading partners in Tovias (), Gremmen (), Dollar and Wolff (), Mokhrari and Rassekh (), O'Rouke and Williamson () and Rassekh () as reviewed by Rassekh and Thompson (). Leamer and Levinshon () and Leamer () find evidence for rising wages in labor scarce developed countries.…”
Section: Introductionmentioning
confidence: 98%
“…The empirical literature on wage convergence in factor proportions models generally focuses on the level of trade rather than product prices. This literature reviewed by Rassekh and Thompson (1998) includes Tovias (1982), Gremmen (1985), Dollar and Wolff (1988), Mokhtari and Rassekh (1989), O'Rourke and Williamson (1992), Rassekh (1992), Leamer and Levinshon (1995), and Leamer (1996). The present paper takes a more direct approach to the Stolper-Samuelson theory linking wages to product prices by directly estimating the factor proportions model.…”
Section: Introductionmentioning
confidence: 99%